Honey bee populations of the USA display restrictions in their mtDNA haplotype diversity - Alburaki, Mohamed; Madella, Shayne; Lopez, Jillian; Bouga, Maria; Chen, Yanping; vanEngelsdorp, Dennis (Frontiers in Genetics, 2023)
The genetic diversity of the USA’s honey bee (Apis mellifera L.) populations was examined through a molecular approach using two mitochondrial DNA (mtDNA) markers. A total of 1,063 samples were analyzed for the mtDNA intergenic region located between the cytochrome c oxidase I & II (COI-COII) and 401 samples were investigated for the NADH dehydrogenase 2 (ND2) coding gene. The samples represented 45 states, the District of Colombia and two territories of the USA. Nationwide, three maternal evolutionary lineages were identified: the North Mediterranean lineage C (93.79%), the West Mediterranean lineage M (3.2%) and the African lineage A (3.01%). A total of 27 haplotypes were identified, 13 of them (95.11%) were already reported and 14 others (4.87%) were found to be novel haplotypes exclusive to the USA. The number of haplotypes per state/territory ranged between two and eight and the haplotype diversity H ranged between 0.236 - 0.763, with a nationwide haplotype diversity of 0.597. Furthermore, the honey bee populations of the USA were shown to rely heavily (76.64%) on two single haplotypes (C1=38.76%, C2j=37.62%) of the same lineage characterizing A. m. ligustica and A. m. carnica subspecies, respectively. Molecular-variance parsimony in COI-COII and ND2 confirmed this finding and underlined the central and ancestral position of C2d within the C lineage. Moreover, major haplotypes of A. m. mellifera (M3a, M7b, M7c) were recorded in six states (AL, AR, HI, MO, NM and WA). Four classic African haplotypes (A1e, A1v, A4, A4p) were also identified in nine states and Puerto Rico, with higher frequencies in southern states like LA, FL and TX. This data suggests an urgent need to enhance the maternal genetic diversity of the US honey bee populations.